The Role of ADMA in Various Diseases - Sofna Banjarnahor; Reny Damayanti (Cermin Dunia Kedokteran, 2023)
Asymmetric dimethylarginine (ADMA) is a competitive inhibitor of nitric oxide synthase (NOS). Numerous studies have discovered a correlation between high plasma ADMA levels and the development of multiple diseases, including cardiovascular disease, chronic renal disease, diabetes mellitus, liver diseases, preeclampsia, and COVID-19. In addition, ADMA has been established as an independent cardiovascular risk factor. However, the functional interplay between ADMA and nitric oxide (NO)-mediated pathways is poorly understood, leaving the distinction between “risk factor” and “risk marker” unclear. In this review, we provide insights into the current state of knowledge regarding the pathophysiological role of ADMA in various diseases, the relationship between ADMA and endothelial dysfunction, the current analytical techniques used to determine ADMA in body fluids, and the benefits of ADMA-lowering drugs for the prevention of diseases in humans.   Asymmetric dimethylarginine (ADMA) adalah penghambat kompetitif nitric oxide synthase (NOS). Banyak penelitian menemukan hubungan antara peningkatan kadar plasma ADMA dan perkembangan berbagai penyakit, termasuk penyakit kardiovaskular, penyakit ginjal kronik, diabetes melitus, penyakit hati, preeklampsia, dan COVID-19. ADMA juga diidentifikasi sebagai faktor risiko independen untuk penyakit kardiovaskular. Namun, interaksi fungsional antara ADMA dan nitric oxide (NO) belum begitu dipahami, yang menyebabkan tidak jelasnya batasan antara “faktor risiko” dan “penanda risiko”. Tulisan ini membahas pengetahuan terbaru tentang peran patofisiologi ADMA dalam berbagai penyakit, hubungan antara ADMA dan disfungsi endotelial, teknik analisis terkini untuk pemeriksaan kadar ADMA dalam cairan tubuh, serta manfaat obat penurun ADMA untuk pencegahan penyakit pada manusia.